Market Relocation of Medan Labuhan - M. J. I. Nasution; Nelson Siahaan (International Journal of Architecture and Urbanism, 2018)
With the needs of the growing community in the District of Medan Labuhan impact on improving people's living standards & population growth. The increase is also in line with the growing demand of the provision of facilities and infrastructure because the higher the level of life of a person, the higher the demands on the provision of facilities, especially in service facilities and commerce. Therefore it is needed a container that can meet the needs of the place of shopping which is realized through "Market Relocation of Medan Labuhan" to buy and sell a place in Medan Labuhan. It aims to improve the economic level of the community in Medan Labuhan. With the formulation of the concept of traditional market orientation of the community as its users, it is expected to increase the attractiveness of the traditional market which can then increase the competitiveness between traditional markets and modern markets. The application of Neo Vernacular is aligned with the design of the building to achieve a balance between buildings, nature, and users.